EFFICACY OF COLISTIN AND CEFIDEROCOL ON CARBAPENEM RESISTANT Acinetobacter baumannii ISOLATES - Feyza Balci; Nilgün Kansak; Sebahat Aksaray (Journal of Global Antimicrobial Resistance)
AIM: To determine the susceptibility rates of colistin and cefiderocol of carbapenem-resistant Acinetobacter baumannii (CRAB) isolates from our center. BACKGROUND: CRAB infections are difficult to manage due to limited treatment options and high mortality rates in critically ill patients. Currently, colistin with combinations is the main option. Recently, cefiderocol has been FDA-approved for the treatment of carbapenem-resistant gram-negative bacterial infections. METHODS: We included 53 CRAB isolates obtained from clinical samples during twelve month period. The isolates were identified using MALDI-TOF MS (bioMérieux). Colistin susceptibility was assessed with broth microdilution. Cefiderocol susceptibility was determined with disk diffusion method using a 30 µg disk (Thermo Scientific™ Oxoid™). Results were evaluated after 18-20 hours of incubation, according to EUCAST v.14.0 guidelines. For colistin, isolates with MIC ≤ 2 mg/L were considered susceptible.Both EUCAST (≥17 mm) and CLSI (≥15 mm) criteria were used for cefiderocol zone diameters. Isolates with zone diameters above the threshold were considered susceptible; those below the threshold were indeterminate due to potential resistance or intermediate susceptibility (Figure 1). RESULTS: All isolates were susceptible to colistin. 68% of isolates were susceptible to cefiderocol (Figure 2). CONCLUSIONS: The absence of colistin-resistant isolates in our study is encouraging. Cefiderocol susceptibility studies for CRAB infections show varying results with different disks and media. In our study, 32% of the isolates could not be evaluated. To accurately assess cefiderocol susceptibility, there is a need for commercial BMD-based tests and/or automated systems, due to challenges in preparing reference BMD in routine conditions.